2015
DOI: 10.4317/jced.52266
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Pyruvic acid in serum and saliva among healthy and potentially malignant disorder subjects - a stepping stone for cancer screening?

Abstract: Background According to Warburg’s effect, the rate of glycolysis increases in cancerous cells. This will increase overall levels of pyruvic acid. The present on-going study was conducted to estimate the levels of pyruvic acid in saliva and serum in normal, oral PMD subjects. Material and Methods A total of 50 subjects in healthy, PMD of the oral cavity individuals were selected based on clinical and histological criteria. Collected saliva and serum samples were subjected to pyruvic acid level estimation using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Salivary pyruvic acid level for healthy individuals was found to be 1.46 ± 0.64,[ 12 ] which is in parallel with this study (1.32 ± 0.10). This is slightly higher than the serum levels, one of the reasons may be the presence of oral bacteria.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Salivary pyruvic acid level for healthy individuals was found to be 1.46 ± 0.64,[ 12 ] which is in parallel with this study (1.32 ± 0.10). This is slightly higher than the serum levels, one of the reasons may be the presence of oral bacteria.…”
Section: Discussionsupporting
confidence: 85%
“…[ 9 ] However, whether the increase of glycolytic activity in cancer cells is mainly due to inherent metabolic alterations or due to the anaerobic environment in the tumor tissues remains controversial[ 10 11 ] Potentially malignant disorders also showed a significant increase of pyruvic acid levels. [ 12 ] Hence, there is a chance of imbalance in the production and excretion of the pyruvic acid in the local and systemic aspects of oral cancer subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The results are tabulated in Tables 1 and 2 . [ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bhat et al . [ 29 ] estimated the serum pyruvic acid levels in healthy and potentially malignant disorder (PMD) subjects and concluded that there was a significant rise in serum pyruvic acid levels in PMD subjects compared to healthy individuals, indicating that estimation of serum pyruvic acid can be a screening tool for PMD and malignant diseases.…”
Section: Discussionmentioning
confidence: 99%